Robot-assisted conversion of ureterocutaneous stoma to ileal conduit: a novel option for patients with post-cystectomy cutaneous diversion complicated by ureteral stricture and recurrent infections - Gu, Tengfei; Chen, Ting; Pan, Yongtao; Yu, Qinzhou; Li, Jie (Frontiers in Urology, 2025)
BackgroundRadical cystectomy accompanied by urinary diversion remains the standard surgical intervention for individuals diagnosed with muscle-invasive bladder cancer. Notably, around 30% of these patients opt for a ureterocutaneous stoma. However, this technique is frequently associated with complications such as anastomotic stenosis, obstruction, and infection, which can lead to the deterioration of renal function and significantly impair the patient’s quality of life. Consequently, this study investigates the safety of robot-assisted laparoscopic conversion from a ureterocutaneous stoma to an ileal conduit stoma, thereby offering a novel surgical alternative for patients undergoing total cystectomy with ureterocutaneous stoma.MethodsA retrospective analysis was carried out on two patients who underwent total cystectomy and ureterocutaneous stoma and were admitted to our hospital in January 2025. We performed robot-assisted laparoscopic conversion of the ureterocutaneous stoma to an ileal conduit for these patients and subsequently evaluated the clinical benefits and surgical safety associated with the procedure.ResultBoth patients successfully underwent surgery, with operation durations of 293 minutes and 281 minutes, respectively. Intraoperative blood loss was recorded at 100 ml and 50 ml, respectively. Abdominal drainage tubes were removed five days postoperatively, and both patients were discharged seven days following the procedure. No surgery-related complications were observed during the perioperative period. Ureteral stents were removed two months post-surgery. Post-extubation CT scans indicated a resolution of the initial mild hydronephrosis in the kidneys. Renal function assessments, including creatinine levels and glomerular filtration rate, demonstrated improvement compared to preoperative values. Additionally, patients reported lower pain scores and higher quality of life scores postoperatively compared to preoperative assessments.ConclusionRobot-assisted laparoscopic ureterocutaneostomy to ileal channel surgery is both feasible and safe, offering potential improvements in renal function and quality of life for patients. Additionally, it presents an alternative surgical option for those requiring ureterocutaneostomy.